Validação do histórico de tratamento endodôntico autorreportado em uma subpopulação urbana do sul do Brasil : um estudo multicêntrico - Koppe, Barbara Thereza de Freitas (2019)
Diagnostic and screening tests are essential tools for determining accurate estimates of diseases, understanding their etiology and transmission patterns. In order to have appropriate validity, a test’s performance should be compared in a variety of populations and settings. Self-reported health status has proved to be a low cost, effective test to assess various general and oral conditions. Especially in the field of Endodontics, they can be useful in replacing the need for radiographs in epidemiological studies. Self-reported history of endodontic treatment (SRHET) has been used as a method of identifying an individual’s experience with endodontic disease and treatment, but only in highly educated male populations. The aim of this multicenter study was to evaluate the validity of SRHET for endodontic treatment (ET) and apical periodontitis (AP) in a subpopulation of first-time patients at universities in two different cities in the South of Brazil. Main exposure SRHET was collected through questionnaire for 228 participants and outcomes ET and AP were assessed by analysis of panoramic radiographs. Data collected included total number of teeth and number of teeth with ET and/or AP for each participant. Validities of SRHET for presence of ET and AP were calculated separately through values of accuracy, sensitivity, specificity, positive and negative predictive values (PPV and NPV), efficiency and positive and negative likelihood ratios (PLR and NLR). Final sample comprised 198 individuals for ET analysis and 192 for AP analysis, after exclusions. The SRHET values were: accuracy (ET=0.858; AP=0.474); sensitivity (ET=0.954; AP=0.739); specificity (ET=0.671; AP=0.250); PPV (ET=0.850; AP=0.454); NPV (ET=0.882; AP=0.530); efficiency (ET=0.812; AP=0.494); PLR (ET=2.899; AP=0.985); NLR (ET=0.068; AP=1.004). SRHET is a valid method for predicting ET, but not for AP in this population. Values of most measures calculated varied in this population in comparison to previous studies. SRHET thus showed to be context-dependent and should be tested in a variety of other populational settings in order to allow its use in future large-scale epidemiological studies including endodontic variables.